Environmental and economic sustainability of poultry litter gasification for electricity and heat generation. (15th July 2019) - Jeswani, Harish Kumar; Whiting, Andrew; Martin, Alastair; Azapagic, Adisa
Highlights: Energy from poultry litter has 90% lower global warming potential than natural gas. Most of other environmental impacts are also reduced by more than 50%. It also performs better than woodchips and Miscanthus for most of the impacts. Gasification of poultry litter in the UK could save 1.7 Mt CO2 eq./yr. With the current subsidies for heat in the UK, the system can pay off in 13.5 years. Abstract: This work aims to assess the environmental and economic sustainability of poultry litter gasification for heat and electricity generation. The results are compared with gasification of two other biomass feedstocks (Miscanthus and waste wood) and energy from fossil fuels. The findings suggest that poultry litter gasification can lead to significant reductions in 14 out of 16 impacts considered in the study in comparison with fossil-fuel alternatives. Compared to combined heat and power (CHP) from natural gas, most impacts from gasification of the litter are lower by more than 90%, including global warming potential. However, human toxicity and depletion of minerals are 25% and three times higher, respectively. Energy from poultry litter also has lower impacts than from waste woodchips and Miscanthus across all the categories, except for acidification. Owing to high capital costs, the unsubsidised cost of generating heat and electricity from poultry litter is similar to that of natural gas CHP but significantly cheaper than from other fossil-fuel alternatives. However, with the current subsidies in the UK, the payback time for poultry litter gasification is 13.5 years. It is estimated that 4.55 Mt of poultry litter is currently available in the UK, 2.73 Mt of which is suitable for conversion to energy. If this waste is utilised in gasification plants, it could potentially provide 0.6% of electricity and heat in the UK and save 1.7 Mt of GHG per year, equivalent to around 0.4% of UK's GHG emissions. However, the successful uptake of this technology will depend on a future reduction in capital costs.